P166 Evidence for state dependent direct effects of alpha band transcranial alternating current stimulation. Issue 3 (March 2017) - Ruhnau, P.; Neuling, T.; Fuscá, M.; Herrmann, C.S.; Demarchi, G.; Weisz, N.
Abstract : Introduction: Transcranial alternating current stimulation (tACS) is used to modulate brain oscillations to measure changes in cognitive function. It is only since recently that brain activity in human subjects during tACS can be investigated. Objectives: In the current study we examine entrainment effects caused by tACS at the individual alpha frequency (IAF) in humans. Material & methods: We analyze magnetoencephalographic (MEG) data transformed to source space following a method we recently showed to diminish the tACS artifact, which makes analysis of brain activity during tACS possible. Using source level data from our previous study here we investigate the phase relationship (coherence) between the external tACS and the neural signal in two resting state condition. Results: We find proof of entrainment in visual cortex areas. Interestingly, this entrainment is only significant when subjects had their eyes open; visual areas were not significantly entrained to tACS when subjects closed their eyes. Furthermore, we find considerable variation across subjects in the delay between tACS and the entrained brain activity. Conclusion: In conclusion, tACS at individual alpha frequency entrains brain activity in visual cortices, however, in a state dependent manner as this effect can only clearly be observed with eyes open.